ASSESSMENT OF VARIOUS KINESIOTHERAPY TREATMENT APPROACHES IN REDUCING POSTOPERATIVE PAIN IN PATIENTS WITH KNEE JOINT ARTHROPLASTY - Bardak, Milica (HEALTH CARE, 2023)
The aim of this review is to analyze various kinesiotherapy treatment approaches in reducing postoperative pain in patients with knee joint arthroplasty. Knee osteoarthritis often causes pain and reduced mobility, which can be alleviated by total knee joint arthroplasty. Based on previous research, it is observed that preoperative strength training improves functionality and range of motion one to three months after surgery. Some studies indicate that rehabilitation, which includes preoperative strength training, results in decreased pain in patients with total knee joint arthroplasty. Also, some studies suggest an increase in pain intensity 9 days after surgery, which gradually decreases in the following days. Gender, BMI, and knee deformity are associated with higher postoperative pain intensity. Although preoperative strength training has a positive impact on functional recovery and range of motion, its effect on reducing postoperative pain requires further investigation. Previous research highlights the need for personalized rehabilitation approaches for patients undergoing total knee joint arthroplasty, taking into account the complexity of pain and various risk factors for postoperative pain occurrence. The development of personalized rehabilitation protocols may provide significantly better recovery outcomes for patients after total knee joint arthroplasty compared to traditional standard approaches.